Char combustion in a packed bed reactor. - Ryan, Jennifer S. (University of Ottawa (Canada), 2000)
This study reports on overfeed packed bed char combustion experiments and modelling. Experimental results are used to verify the assumptions of an existing char combustion simulation. The computer model uses finite volume discretization methods to predict temperature and concentration profiles for packed bed char combustion. Also, the behaviour of ash in a packed bed is explored and incorporated into the model by accounting for the effect of ash on such properties as bed void fraction and heat and mass transfer processes. The effects of air flow rate and bed depth on the burning rate, the bed temperature and gas concentrations are also examined. Experiments were performed in a reactor 23 cm in diameter and 20 cm high. Thermocouples measured bed temperatures and a water-cooled probe sampled bed gases. Gas samples were analysed for CO2, CO and O2 using a gas chromatograph. The fuel was foundry coke with a particle diameter in the 1 cm size range. Experiments were run for bed heights ranging from 5 to 15 cm and air flow rates of 191 to 520 kg/m2hr. Comparison of the experimental bed profiles and burning rates with model predictions shows good agreement, indicating that the model can reliably predict packed bed char combustion. Species concentrations are shown to be only dependent on bed depth; whereas the burning rate is a function of both the bed depth and air flow rate. The data also show that the ash properties are highly dependent on the operating conditions; since the model predictions are very sensitive to the ash properties, a relationship between ash properties and temperature needs to be developed and included in the model. More research is also needed on the CO2 reduction reaction parameters and pore diffusion model and the oxidation kinetics in the ash layer.
Keywords: Engineering, Chemical.